PHYSIOLOGICAL AND PSYCHOLOGICAL CHARACTERISTICS AMONG COMPETITIVE ROWERS - Alföldi, Zoltán; Katona, Zsolt Bálint; Gyömörei, Tamás; Kósa, Lili; Ihász, Ferenc (Stadium - Hungarian Journal of Sport Sciences, 2022)
Introduction: Elite rowing athletes participated in anthropometric, psychological and physiological tests.Aim: This study aimed to investigate the relations between the traits of sport-confidence and competitive orientation, as well as to compare state measures of sport-confidence, self-efficacy and anxiety. Furthermore, this study targeted to examine the associations of these state measures with performance, in our case the 2000m rowing ergometer run time.Material and methods: Rowers (N=15) were subjected to anthropometric, psychological and physiological tests: max 2000 m on Rowing Ergo-test, Athletic Coping Skills Inventory-28, Competitive State Anxiety Inventory-2 and Sport Competition Anxiety Test.Results: CSAI-self-confidence showed a statistically significant difference between genders with boys having a higher score. Overall, SCAT (anxiety) scores were low (normal anxiety) in the sample for the vast majority (12 rowers), only 3 participants showed high anxiety. Conclusion: The psychological profile does not contribute significantly performance on 2000m Rowing Ergo-test but affects it. Girls completed the distance in a longer period of time, and cognitive anxiety was relatively greater among girls. Additionally, our study pointed out that if the physical parameters are 'inadequate,' then the psychological profile does not contribute to better performance.